2016
DOI: 10.2337/db15-0662
|View full text |Cite
|
Sign up to set email alerts
|

A Synergistic Antiobesity Effect by a Combination of Capsinoids and Cold Temperature Through Promoting Beige Adipocyte Biogenesis

Abstract: Beige adipocytes emerge postnatally within the white adipose tissue in response to certain environmental cues, such as chronic cold exposure. Because of its highly recruitable nature and relevance to adult humans, beige adipocytes have gained much attention as an attractive cellular target for antiobesity therapy. However, molecular circuits that preferentially promote beige adipocyte biogenesis remain poorly understood. We report that a combination of mild cold exposure at 17°C and capsinoids, a nonpungent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 56 publications
3
62
1
5
Order By: Relevance
“…However, it has recently been found that capsinoids (non-pungent analogues of capsaicin), through an activation of β2-AR, also induce WAT browning and PRDM16 protein stabilization in subcutaneous WAT 104 . It is conceivable that other hormonal stimuli — such as BMP7 (REFS 105,106), a newly identified myokine, irisin 107 , fibroblast growth factor 21 (FGF21) 108,109 and natriuretic peptides 91 — may also induce WAT browning through this mechanism.…”
Section: Regulation By External Cuesmentioning
confidence: 99%
“…However, it has recently been found that capsinoids (non-pungent analogues of capsaicin), through an activation of β2-AR, also induce WAT browning and PRDM16 protein stabilization in subcutaneous WAT 104 . It is conceivable that other hormonal stimuli — such as BMP7 (REFS 105,106), a newly identified myokine, irisin 107 , fibroblast growth factor 21 (FGF21) 108,109 and natriuretic peptides 91 — may also induce WAT browning through this mechanism.…”
Section: Regulation By External Cuesmentioning
confidence: 99%
“…Interestingly, capsinoids associated with physical exercise blocked diet‐induced obesity by increasing energy consumption, even though this effect has been attributed to TRPA1 receptor . More recently, a synergistic antiobesity effect by a combination of capsinoids and cold temperature through promoting beige adipocyte biogenesis has been observed …”
Section: Pathophysiological Rolesmentioning
confidence: 99%
“…This was confirmed by increased BAT and beige specific gene markers such as Ucp1, Pgc1α, Cidea, Cd137, and Tmem26 , in inguinal WAT, respectively. It has been shown that capsinoids upregulated the expression of the PRDM16 protein in inguinal WAT under ambient and mildly cold temperatures upon β-adrenergic stimulation [95]. Yoneshiro et al demonstrated that acute administration of capsinoids increased energy expenditure in BAT-positive subjects, but not in subjects without metabolically active BAT, under cold exposure [96].…”
Section: Phytochemicals In Obesitymentioning
confidence: 99%